Evaluation of automation levels for construction change management. Issue 5 (19th September 2016) - Karimidorabati, Shahin; Haas, Carl T.; Gray, Joel
Abstract : Purpose: Current processes to manage changes are subject to failure since they are heavily dependent on human discipline. The purpose of this paper is to evaluate and quantify the difference between levels of automation of change management processes and to provide input for determining the use of automation systems for change management. Design/methodology/approach: Three generations of change management processes are defined to represent progressive practices used in major capital projects over the past few decades. Discrete event simulation was used to model these processes to capture their behavior and compare their performance according to time and compliance metrics. An oil and gas megaproject served to validate the findings of this modeling and analysis. Findings: The results showed that automated processes can bring more compliance and real-time traceability, but not a significant time reduction in the change process. This contributes to the understanding of the impact of workflow-based automation on construction process performance. The validity of the conclusions are limited by the breadth of sectors studied and the inability to capture off-line time allocations of the personnel involved. Future research may build on the work presented here by studying additional processes such as requests for information, project change notices, requests for scaffolding, and interface management in various industry sectors. Originality/value: A new approach for modeling and evaluating construction management process automation is contributed and the specific results of the paper indicate that automated workflow-based change management processes should be implemented in megaprojects.